Field notes contributed by George E. Crossley, spring 1980 - Crossley, George E.et al (1980)
List of birds and locations contributed by George E. Crossley. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed